N‐Cadherin/Wnt Interaction Controls Bone Marrow Mesenchymal Cell Fate and Bone Mass During Aging. Issue 11 (November 2014) - Haÿ, Eric; Dieudonné, François‐Xavier; Saidak, Zuzana; Marty, Caroline; Brun, Julia; Da Nascimento, Sophie; Sonnet, Pascal; Marie, Pierre J.
Abstract Age‐related bone loss is characterized by reduced osteoblastogenesis and excessive bone marrow adipogenesis. The mechanisms governing bone marrow mesenchymal stromal cell (BMSC) differentiation into adipocytes or osteoblasts during aging are unknown. We show here that overexpressing N‐cadherin (Cadh2) in osteoblasts increased BMSC adipocyte differentiation and reduced osteoblast differentiation in young transgenic (Tg) mice whereas this phenotype was fully reversed with aging. The reversed phenotype with age was associated with enhanced Wnt5a and Wnt10b expression in osteoblasts and a concomitant increase in BMSC osteogenic differentiation. Consistent with this mechanism, conditioned media from young wild type osteoblasts inhibited adipogenesis and promoted osteoblast differentiation in BMSC from old Cadh2 Tg mice, and this response was abolished by Wnt5a and Wnt10b silencing. Transplantation of BMSC from old Cadh2 Tg mice into young Tg recipients increased Wnt5a and Wnt10b expression and rescued BMSC osteogenic differentiation. In senescent osteopenic mice, blocking the CADH2–Wnt interaction using an antagonist peptide increased Wnt5a and Wnt10b expression, bone formation, and bone mass. The data indicate that Cadh2/Wnt interaction in osteoblasts regulates BMSC lineage determination, bone formation, and bone mass and suggest a therapeutic target for promoting bone formation in the aging skeleton. J. Cell. Physiol. 229: 1765–1775, 2014. © 2014 Wiley Periodicals, Inc.